Straw Man Fallacy of the Complete Conversation System Claim against the Turing Test (Diametros, 2024)
This paper aims to present and discuss an argumentation against the Turing test (TT), which we shall call the CCSC (Complete Conversation System Claim). Exemplary arguments of the CCSC type include Lem’s “Space Gramophone,” the “machine equipped with a dictionary” proposed by Shannon and McCarthy, Block’s “Aunt Bubbles,” and Searle’s “Chinese Room” argument. CCSC argumentation is constructed to show that the TT is not properly designed and, consequently, is not a good hallmark of intelligence. Based on the original TT rules reconstruction, I argue that CCSC-type argumentation seems to be aimed at a certain interpretation of the TT, which, as I demonstrate, commits the straw man fallacy. In light of the results presented by Łupkowski and Wiśniewski, I also discuss whether a complete conversation system is theoretically possible.
Keywords: Turing test; intelligence; logic of questions; conceptual foundations of AI; argumentation